Development of an electrochemical sensor for determination of dissolved oxygen by nickel-salen polymeric film modified electrode - Martin, Cibely S. [UNESP]; Dadamos, Tony R. L. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Elsevier B.V. Sa, 2012)
An amperometric oxygen sensor based on a polymeric nickel-salen (salen = N,N'-ethylene bis(salicylideneiminato)) film coated platinum electrode was developed. The sensor was constructed by electropolymerization of nickel-salen complex at platinum electrode in acetonitrile/tetrabutylammonium perchlorate by cyclic voltammetry. The voltammetric behavior of the sensor was investigated in 0.5 mol L-1 KCl solution in the absence and presence of molecular oxygen. Thus, with the addition of oxygen to the solution, the increase of cathodic peak current (at -0.25 V vs. saturated calomel electrode (SCE)) of the modified electrode was observed. This result shows that the nickel-salen film on electrode surface promotes the reduction of oxygen. The reaction can be brought about electrochemically, where the nickel(II) complex is first reduced to a nickel(I) complex at the electrode surface. The nickel(I) complex then undergoes a catalytic oxidation by the molecular oxygen in solution back to the nickel(II) complex, which can then be electrochemically re-reduced to produce an enhancement of the cathodic current. The Tafel plot analyses have been used to elucidate the kinetics and mechanism of the oxygen reduction. A plot of the cathodic current vs. the dissolved oxygen concentration for chronoamperometry (fixed potential = -0.25 V vs. SCE) at the sensor was linear in the 3.95-9.20 mg L-1 concentration range and the concentration limit was 0.17 mg L-1 O-2. The proposed electrode is useful for the quality control and routine analysis of dissolved oxygen in commercial samples and environmental water. The results obtained for the levels of dissolved oxygen are in agreement with the results obtained with a commercial O-2 sensor. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Oxygen sensor; Electrochemical behavior; Polymeric nickel-salen; Amperometry; Oxygen reduction